Learning Fourier series with parametrized quantum circuits - Dirk Heimann; Hans Hohenfeld; Gunnar Schönhoff; Elie Mounzer; Frank Kirchner (Physical Review Research)
Variational quantum algorithms (VQAs) and their applications in the field of quantum machine learning through parametrized quantum circuits (PQCs) are thought to be one major way of leveraging noisy intermediate-scale quantum computing devices. However, differences in the performance of certain VQA architectures are often unclear since established best practices, as well as detailed studies, are missing. In this paper, we build upon the work by Schuld et al. [Phys. Rev. A 103, 032430 (2021)2469-992610.1103/PhysRevA.103.032430] and Vidal et al. [Front. Phys. 8, 297 (2020)2296-424X10.3389/fphy.2020.00297] by comparing how well popular ansatz for PQCs learn different one-dimensional truncated Fourier series. We also examine dissipative quantum neural networks (dQNN) as introduced by Beer et al. [Nat. Commun. 11, 808 (2020)2041-172310.1038/s41467-020-14454-2] and propose a data reupload structure for dQNNs to increase their capability for this regression task. By comparing the results for different PQC architectures, we can provide guidelines for designing efficient PQCs.